Use of alcohol fixed cytospins protected by 10% polyethylene glycol in immunocytology external quality assurance. Issue 2 (1st February 1999) - Maxwell, P; Patterson, A H; Jamison, J; Miller, K; Anderson, N
Abstract : AIMS: To provide cytospins as a means of external quality assurance (EQA), while maintaining antigen expression integrity and achieving uniformity of material for all participating laboratories. METHODS: Cells were collected from two adenocarcinoma and one reactive pleural effusion specimens. Lymphoid cells were also collected through aspiration of a resected tonsil specimen. All cells were collected in Hanks balanced salt solution (HBSS); cytospins were made and fixed in methanol or acetone alone or protected using a layer of 10% polyethylene glycol (PEG) in 50% methanol. Two laboratories participated (RGHT and UCL). RESULTS: Cytokeratin expression detected using either CAM5.2 or AE1/AE3 antibodies was sensitive to temperature. Without PEG, unacceptable or negative staining was seen within six weeks of preparation. LCA was not sensitive to temperature, with good staining scores being achieved after eight weeks following preparation. CONCLUSIONS: It is possible to send alcohol fixed, air dried cytospins to laboratories participating as part of an EQA scheme for immunocytology. Some antigens will require protection from temperature variations during transit. A layer of 10% PEG in 50% methanol, allowed to air dry, is suitable for this purpose. Participating laboratories will only have to remove this layer using methanol before their localisation technique for assessment.